Whole-Genome Phylogenetic Reconstruction as a Powerful Tool to Reveal Homoplasy and Ancient Rapid Radiation in Waterflea Evolution. (23rd November 2021) - Van Damme, Kay; Cornetti, Luca; Fields, Peter D; Ebert, Dieter
Abstract: Although phylogeny estimation is notoriously difficult in radiations that occurred several hundred million years ago, phylogenomic approaches offer new ways to examine relationships among ancient lineages and evaluate hypotheses that are key to evolutionary biology. Here, we reconstruct the deep-rooted relationships of one of the oldest living arthropod clades, the branchiopod crustaceans, using a kaleidoscopic approach. We use concatenation and coalescent tree-building methods to analyze a large multigene data set at the nucleotide and amino acid level and examine gene tree versus species tree discordance. We unequivocally resolve long-debated relationships among extant orders of the Cladocera, the waterfleas, an ecologically relevant zooplankton group in global aquatic and marine ecosystems that is famous for its model systems in ecology and evolution. To build the data set, we assembled eight de novo genomes of key taxa including representatives of all extant cladoceran orders and suborders. Our phylogenetic analysis focused on a BUSCO-based set of 823 conserved single-copy orthologs shared among 23 representative taxa spanning all living branchiopod orders, including 11 cladoceran families. Our analysis supports the monophyly of the Cladocera and reveals remarkable homoplasy in their body plans. We found large phylogenetic distances between lineages with similar ecological specializations, indicating independent evolution in major body plans, such as in the pelagic predatory orders Haplopoda and Onychopoda (the "Gymnomera"). In addition, we assessed rapid cladogenesis by estimating relative timings of divergence in major lineages using reliable fossil-calibrated priors on eight nodes in the branchiopod tree, suggesting a Paleozoic origin around 325 Ma for the cladoceran ancestor and an ancient rapid radiation around 252 Ma at the Perm/Triassic boundary. These findings raise new questions about the roles of homoplasy and rapid radiation in the diversification of the cladocerans and help examine trait evolution from a genomic perspective in a functionally well understood, ancient arthropod group. [Cladocera; Daphnia ; evolution; homoplasy; molecular clock; phylogenomics; systematics; waterfleas.]